POLA PRINSIP KEMITRAAN DALAM PENGEMBANGAN PARIWISATA DI KABUPATEN PURBALINGGA PROVINSI JAWA TENGAH - Daraba, Dahyar; Murwani, Sari Indah; Dione, Frans; Salam, Rudi (FIA UB, 2020)
In the development of tourism in the region requires planning, strategy and innovation where managers and governments must seriously develop their regional tourism sector to improve the regional economy and society is descriptive qualitative with an inductive approach. Sources of data obtained from primary and secondary data. Data collection is done by observation, interviews, and documentation. Data analysis techniques through data reduction, data presentation, and drawing conclusions. The results showed that the partnership pattern in the development of tourism in Purbalingga District had gone quite well but not yet at maximum. This is stated by fulfilling the 3 principles of partnership namely mutual respect, respect and trust. To realize partnerships in tourism it is necessary to agree on the perception of partnerships between the private sector, the government and the community